Per operative discovery of Placenta Praevia Percreta: a case report - Lawrence Mbuagbaw; Frederick Lifangi-Ikomi Morfaw (The Pan African Medical Journal, 2013)

(untitled)
Placenta percreta is a rare pathological entity with challenging diagnostic and therapeutic requirements especially for resource limited settings. We present here the case of a 40 year old woman with a per operative diagnosis of placenta accreta during a caesarian section indicated for placenta praevia. We highlight the diagnostic and therapeutic difficulties associated with this condition especially in low resource settings. Physicians performing caesarian sections should be prepared for complex intra-operative findings in high risk patients.